TRENDS OF FOOD AND WINE PAIRATION IN THE WORLD AND DEVELOPMENT OF GASTROENOLOGICAL OFFERS IN RESTAURANTS IN SERBIA - Jankovic, Ivana; Ćirić, Miloš (The Business of Tourism, 2021)
Food and wine have long been a synergistic blend. The task of this paper is to determine which characteristics influence the formation of the gastronological experience. The aim of this paper is a researcher in which measures are used in Serbia at home and in which there are foreign wines and which are characterized by important segments for the formation of good gastroenolic offers. According to the research on gastronomic offer that was processed in this research, it is clear that there is a lot of foreign wines in restaurants, as a guideline for development in the field of harmonization of food and wine, more emphasis should be given to domestic dishes and domestic wines. This certainly contributes to the development of small businesses and local growers to better place and promote both domestic guests and tourists. Belgrade, as the capital of the Republic of Serbia and as the main tourist destination, should adjust the offer of both food and wine in its restaurants. There are tourists whose primary goal of travel is a gastronomic experience, they want to try as much localized food and wine as possible. While there are also those whose primary goal is not gastroenology when traveling and they want to consume something familiar to them. Restaurants or other catering facilities should definitely be adapted to both domestic guests and tourists in order to satisfy the guest.